Thermal analysis of partitioned electric water heaters for energy conservation - Yazıcıoğlu, Rıdvan (My University, 2006)
Bu çalısmada elektrikli su ısıtıcılarının optimum dizaynı ve seçimi incelenmistir. Tek bölmeli elektrikli su ısıtıcı ile bölmeli elektrikli su ısıtıcı aynı baslangıç sartlarıyla kıyaslandığında bölmeli elektrikli su ısıtıcının üstteki hacimi toplam hacmin %25 ine ve toplam elektrik gücünün %75 ine sahip olması durumunda daha fazla sıcak su sağladığı ve dolayısıyla enerji tüketiminin azaldığı gözlenmistir. Problemdeki termodinamik diferansiyel denklemlerinin çözümünde Matlab programından yararlanılmıstır. Baslangıç degerleri literature arastırmasından faydalanılarak kabul edilmistir. Insanların günlük sıcak su kullanımında Becker’in ortalama sıcak su profili baz alınmıstır. I

Optimum design and selection of storage type electric water heaters were analyzed for energy conservation. The thermal performance of a single tank electric water heater is compared with that of partitioned electric water heater for the same average domestic hourly hot water use pattern according to Becker’s profile. Both water heaters have the same volume capacity and total power rating while the temperature of the hot water was kept between 60 and 65oC. It is concluded that a partitioned electric water heater provides more hot water and reduces energy consumption where as the upper part of the tank has 25% of the total volume and 75% of the total power rating. To evaluate single tank and partitioned electric water heaters transient energy balance equations have been derived. The differential equations with initial conditions solved using Matlab 7.0 program. Some assumptions made and thermodynamic properties received to use the evaluate differential equations. To represent water heater models equations related data received from literature.
Keywords: Endüstriyel Tasarım; Makine Mühendisliği; Su Isıtıcıları_Tasarım